Enhancing LAN Performance, Fourth Edition - Held, Gilbert (CRC Press, 2009)
Network managers tasked with establishing LANs, expanding or linking networks, and securing user access need a book that explores how to determine throughput rate and bandwidth while controlling network costs. Enhancing LAN Performance, Fourth Edition, explains how to connect geographically separated LANs with appropriate bandwidth, the issues to consider when weighing the use of multiport or dualport devices, how to estimate traffic for new networks, the effects of configuration changes on the performance of Ethernet and Token Ring networks, the design of switch-based networks that prevent traffic bottlenecks, and other topics critical to LAN managers.